1918 S.C. Acts 723, no. 393, § 1 - (:unkn) unknown (My University, 1918)
Provided further, that it shall be unlawful to at any time use any automatic or pump gun while hunting birds in said county. Any person violating any of the provisions hereof shall upon conviction in any Court of competent jurisdiction, be fined not less than ten dollars nor more than twenty dollars, or be imprisoned at hard labor not less than ten days nor more than twenty days for each and every offense.
Keywords: HUNTING REGULATION